1998
DOI: 10.1159/000052036
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Buprenorphine and Methadone in the Treatment of Opioid Dependence

Abstract: A three-centre, randomised, double-blind study was designed to compare the efficacy and safety of buprenorphine and methadone. This was the first European study to compare these agents and was based on a previous trial performed in the US. Opioid-dependent subjects were randomised to receive either sublingual buprenorphine or oral methadone daily. Both objective and subjective measures of efficacy were monitored weekly, and safety parameters were regularly monitored over the entire six-week study. Urinalysis s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(28 citation statements)
references
References 9 publications
2
26
0
Order By: Relevance
“…It reduces withdrawal symptoms (Bickel & Amass, 1995;Chadderton, 2000) and blocks the effects of opiates (Mello & Mendelson, 1980). Numerous clinical trials have been conducted to confirm buprenorphine's effectiveness in the treatment of opiate dependence (Amass et al, 2004;Fischer et al, 1999;Fudula et al, 2003;Johnson et al, 2000;Johnson, Jaffe, & Fudula, 1992;Kosten, Schottenfeld, Ziedonis, & Falconi, 1993;Ling, Wesson, Charuvastra, & Klett, 1996;Lintzeris, Bell, Bammer, Jolley, & Rushworth, 2002;Pani, Maremmani, Piratsu, Tagliamonte, & Gessa, 2000;Petitjean et al, 2001;Schottenfeld, Pakes, Oliveto, Ziedonis, & Kosten, 1997;Strain, Stitzer, Liebson, & Bigelow, 1994;Uehlinger et al, 1998). The Substance Abuse and Mental Health Services Administration [SAMHSA] (2004) has published clinical practice guidelines regarding the use of buprenorphine (see also Johnson, Strain, & Amass, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…It reduces withdrawal symptoms (Bickel & Amass, 1995;Chadderton, 2000) and blocks the effects of opiates (Mello & Mendelson, 1980). Numerous clinical trials have been conducted to confirm buprenorphine's effectiveness in the treatment of opiate dependence (Amass et al, 2004;Fischer et al, 1999;Fudula et al, 2003;Johnson et al, 2000;Johnson, Jaffe, & Fudula, 1992;Kosten, Schottenfeld, Ziedonis, & Falconi, 1993;Ling, Wesson, Charuvastra, & Klett, 1996;Lintzeris, Bell, Bammer, Jolley, & Rushworth, 2002;Pani, Maremmani, Piratsu, Tagliamonte, & Gessa, 2000;Petitjean et al, 2001;Schottenfeld, Pakes, Oliveto, Ziedonis, & Kosten, 1997;Strain, Stitzer, Liebson, & Bigelow, 1994;Uehlinger et al, 1998). The Substance Abuse and Mental Health Services Administration [SAMHSA] (2004) has published clinical practice guidelines regarding the use of buprenorphine (see also Johnson, Strain, & Amass, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, it is buprenorphine that has gained more and more importance in addiction treatment because the correlation between dose and therapeutic effects is not linear, indicating a ceiling on the effects in patients due to its opiate agonistic-antagonistic characteristics [7][8][9]. Buprenorphine is therefore a relatively safe substance, and its effectiveness in maintenance therapy has been proved in many studies [10][11][12][13][14][15][16][17]. It has been used in Austria as a substitution drug since 1999.…”
Section: Introductionmentioning
confidence: 99%
“…Metaanalysis has revealed that buprenorphine was signifi cantly less effective than methadone in retaining patients in treatment [27] . Low retention rates with buprenorphine may be explained by too low a dose being used during the induction period [28] . However, the relatively short duration of the present study, which lasted only 3 weeks, must be also taken into account when considering high retention rates recorded.…”
Section: Discussionmentioning
confidence: 99%